Let’s Get That Bread Clip: Mechanical or Malignant Large Bowel Obstruction? - Molly Clark; Morgan Jones; Joseph Kong (Journal of Acute Care Surgery, 2023)
A 60-year-old female presented with symptoms consistent with a large bowel obstruction (LBO). Following confirmation of LBO using imaging, she progressed to a laparotomy which potentially revealed a large rectosigmoid tumor with surrounding adhesions, deemed unresectable. The postoperative course was complicated by an enterocutaneous fistula. She was transferred to a tertiary center and underwent a repeat laparotomy which revealed a large fibrotic mass associated with an intra-luminal bread clip (expiry date 2002). This case report details the interesting causative nature of this LBO and the subsequent surgical management, and complicated postoperative course.